Enhancing Sustainable Project Performance through Strategic Design Compliance and Scheduling Management - Bukhori; Kartono Wibowo; Antonius (Politeknik APP Jakarta, 2026)
Building projects continue to experience persistent cost overruns, quality inconsistency, and schedule slippage, indicating a lack of integrated managerial mechanisms that translate control practices into sustainable performance outcomes. An integrated monitoring model is empirically tested using SEM–PLS based on survey data from 263 construction practitioners, triangulated with operational project records including Earned Value Management, S-curve analysis, and BIM 4D/5D outputs. The results demonstrate that DES exerts a strong influence on cost and quality performance, COM is the dominant driver of quality stability with indirect cost effects, and SCH is the primary determinant of time performance. The framework contributes by linking managerial control practices to measurable sustainability outcomes, offering a practical project-control architecture particularly relevant for developing-country construction contexts.